The Rise and Fall of German Innovation - Wim Naudé; Paula Nagler (Institute of Labor Economics (IZA), 2021)
In this paper, we describe the historical co-evolution of innovation and economic growth in Germany since 1871. The country's rise as an industrial power in the late 19th century, through its innovation and entrepreneurial performance, is contrasted with the post-World War II period. This latter period, although it contained the German economic miracle, was nevertheless a period during which innovation went into relative decline. We document this decline and offer four broad, interrelated explanations: (i) an innovation system locked into incremental innovation, (ii) a slowdown in the diffusion of technology, (iii) weaknesses in the education system, and (iv) entrepreneurial stagnation. Implications for policy are noted. Our paper contributes to the growing literature attempting to understand the decline in business dynamism that characterises many advanced economies.
Keywords: D31; L26; O33; O38; O52; 330; entrepreneurship; inequality; innovation; productivity; technology